Doris - Cole, Lo (Boxer Books, 2024)
"Being a bright red elephant, Doris is very easy to spot. Can you see her? Exactly. But Doris dreams of losing herself in a colorful crowd. Come on a journey of discover as one little elephant comes to appreciate being herself in this interactive picture book."--Publisher's description.